Reflection, Objectivity, and the Love of God, A Passage from Merleau‐Ponty's Phenomenology of Perception. (22nd February 2010) - Berman, Michael
Abstract : Merleau‐Ponty's Phenomenology of Perception (1945) essentially aims at debunking the myth of objectivity. The Phenomenology takes the entire Western tradition to task over its reliance on the objective attitude, showing how this attitude structures the architectonics of idealism and empiricism. These philosophies share the same presuppositions: their metaphysics and epistemologies are inherently dualistic. The problematics that stem from this objectivism have informed the Western understanding of God. This essay undertakes an examination of one of the more extended treatments of God in Merleau‐Ponty's magnum opus . The aim is not to justify or critique the objective attitude per se, but to show some of its radical implications for theology after Descartes. The passage of focus is on pages 358–9 in the English translation of the Phenomenology . The attempt here is to bring some of the research on Merleau‐Ponty into dialogue with the philosophy of religion, and is a tentative step in a larger project of looking at the role of God in Merleau‐Ponty's corpus.